Ferroelectric properties, narrow band gap and ultra-large reversible entropy change in a novel nonlinear ionic chromium() compound - Han, Ding-Chong; Gong, Zhi-Xiang; Song, Ning; Tan, Yu-Hui; Li, Yu-Kong; Tang, Yun-Zhi; Du, Peng-Kang; Zhang, Hao (Chemical communications (Cambridge, England), 2021)
A novel chromium( vi )-based compound, [(CH 3 CH 2 ) 3 N(CH 2 Cl)][CrO 3 Cl] ( 1 ), undergoes a high-temperature phase transition at around 340.9 K, accompanied by an ultra-large entropy change of 63.49 J mol −1 K −1 . Compound 1 exhibits a moderate ferroelectric polarization of 0.48 μC cm −2 and a remarkable CD signal. Strikingly, 1 occupies a narrow band gap of 2.22 eV, which is chiefly attributed to the inorganic [CrO 3 Cl] − tetrahedron. It is believed that these findings will contribute to an alternative pathway for the design of multifunctional ferroelectric materials, whose potential applications will be in semiconductors, energy storage, etc. A novel nonlinear chromium( vi ) compound, [(CH 3 CH 2 ) 3 N(CH 2 Cl)][CrO 3 Cl], undergoes a high-temperature phase transition with a moderate ferroelectric polarization of 0.48 μC cm −2 , a remarkable CD signal, a giant entropy change and a narrow band gap of 2.22 eV.